Understanding heat energy conservation: using traditional brick making in a Grade 7 Natural Sciences class in a rural school - Godlo, Lindiwe Priscilla (Rhodes University, Faculty of Education, Department of Secondary and Post-School Education)
Learners seemed to experience cognitive dissonance on the topic of the conservation of heat energy. My assumption is that this might be due to cognitive dissonance or conflict that learners seem to experience in science classrooms. This means the way science teachers teach science does not form part of learners' contexts and hence has no relevance to them. To ameliorate this dilemma, the South African Curriculum and Assessment Policy Statement (CAPS) document requires teachers to integrate indigenous knowledge into science teaching and learning but does not provide explicit methods on how to do it. It is against this backdrop that this study explored how the use of traditional brick making method can support learners to make sense of the topic of conservation of heat energy. Underpinned by the interpretivist and Indigenous research paradigms, a qualitative case study design was employed. Twenty-four Grade 7 Natural Sciences learners, four indigenous knowledge custodians (IKCs) (who were all women), and a critical friend participated in this study. Data sets were generated through several methods: learner group activity; participatory and lesson observations; a sharing circle; and learners' reflective journals. Vygotsky's Sociocultural Theory and Ogunniyi's Contiguity Argumentative Theory were used as theoretical lenses to analyse data. The findings revealed that during the demonstration by the IKCs, learners were able to identify science concepts related to the conservation of heat energy which means they understood the science concept. Learners' argumentation and sense-making of the aforementioned topic and related concepts greatly improved. Based on the research findings, I thus recommend that teachers should tap into IKCs' cultural heritage to contextualise and make science relevant and more meaningful to learners.
Keywords: Science-- Study and teaching (Primary) -- South Africa; Traditional ecological knowledge -- South Africa; Social learning -- South Africa; Ubuntu (Philosophy); Heat storage; Brickmaking -- South Africa